Chronological Archery Algorithm for Image Compression Using Compressive Sensing in IoT-LTE System - Sai Venkateshwar Rao, A.; Amgoth, Tarachand; Bhattacharya, Ansuman (IEEE transactions on consumer electronics, 2025)
Recent advancements in information technologies use the Internet of Things (IoT) for various communication tasks. However, many existing works neglect image data compression, especially in smooth regions, leading to higher costs and energy consumption. Additionally, the balance between compressed image and quality was often not achieved. This research proposes an effective data compression and recovery method using the compressive sensing-based image compression FCSP-based Chronological Archery Algorithm (FCSP-based CAA) model for IoT-LTE systems. The process involves three phases: authentication, communication, and data compression. Data security is ensured through authentication, followed by communication using the Low Energy Adaptive Clustering Hierarchy (LEACH) routing protocol. The compressed image data is then recovered by addressing collaborative recovery issues using the proposed Chronological Archery Algorithm (CAA) model. This model is based on an objective function called "Feature similarity, Collaborative sparsity Structural Similarity and Peak signal to noise (FCSP)" measure. Experimental results demonstrate that the proposed methodology achieves enhanced compression performance compared to existing techniques, with a Peak Signal-To-Noise Ratio (PSNR) of 81.876dB, Mean Square Error (MSE) of 0.005, and Structural Similarity Index Measure (SSIM) of 70.876.